Advances in the biosynthesis of naturally occurring benzylisoquinoline alkaloids - Wanli Zhao; Jihua Liu; Yu Chen (Frontiers in Plant Science)
Benzylisoquinoline alkaloids (BIAs) are a prominent class of plant metabolites with significant pharmaceutical and industrial significance that have garnered substantial attention from researchers worldwide. BIAs exhibit several pharmacological activities and have been used extensively. Examples include analgesics such as morphine, tetrahydropalmatine, antimicrobials such as berberine, and antineoplastic agents including cepharanthine. Most BIAs are derived and isolated from medicinal plants; however, these plants are predominantly wild resources that are scarce. Their high environmental impact, slow growth rate, scarcity of resources, and expensive direct extraction costs pose a significant challenge. Certain BIAs are present in trace amounts in medicinal plants; moreover, they have complex chemical structures and unstable properties. Designing chemical synthesis routes and processes is challenging. Thus, a major obstacle in developing and utilizing these natural products in the pharmaceutical industry lies in their low abundance in nature. Consequently, the limited supply of these molecules fails to meet high research and market demands. In recent years, biosynthesis approaches have emerged as a novel and efficient method to obtain BIAs. In this review, recent progress in the field of enzymes related to the elucidation of biosynthetic pathways and the biosynthesis of BIAs are discussed, and future perspectives for designing viable strategies for their targeted manipulation are presented.